2012
DOI: 10.5551/jat.13631
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Circulation Determined by Pulse Wave Analysis is Significantly Correlated with Cardio Ankle Vascular Index, Left Ventricular Diastolic Function, and Age

Abstract: Aim:To determine whether there is a significant correlation between optic nerve head circulation determined by pulse wave analysis of laser speckle flowgraphy (LSFG), and the cardio-ankle vascular index (CAVI), left ventricular (LV) function, and age. Methods: Forty-nine men who visited the Vascular Function Section of Toho University Sakura Medical Center, Chiba, Japan were studied. The mean age of the subjects was 60.7±10.6 years (range 29 to 80 years). The CAVI, left ventricular ejection fraction (LVEF) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
2
48
2
Order By: Relevance
“…Cho et al [77] reported that CAVI combined with age can clinically serve as an objective tool to diagnose blood stasis syndrome in stroke patients. Shiba et al [78] reported that the optic nerve head circulation was significantly correlated with CAVI. This suggests that microcirculation is determined by arterial stiffness.…”
Section: Cavi As An Indicator Of Vascular Functionmentioning
confidence: 99%
“…Cho et al [77] reported that CAVI combined with age can clinically serve as an objective tool to diagnose blood stasis syndrome in stroke patients. Shiba et al [78] reported that the optic nerve head circulation was significantly correlated with CAVI. This suggests that microcirculation is determined by arterial stiffness.…”
Section: Cavi As An Indicator Of Vascular Functionmentioning
confidence: 99%
“…CAVI could be useful for the cardiovascular risk stratification in future guideline of patients with coronary risk factors, although further studies are required to confirm these. Moreover, CAVI has relationships with the left ventricular function 76,77) and retinal artery pulsation 78) . These results suggest that CAVI is an adequate marker of vascular function as Windkessel.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] Our recent study on CSC demonstrates that the macular MBR increases at the acute stage, 19 reinforcing the suspected role of choroidal hyperperfusion in the development of acute CSC. 10 With recent advances of LSFG, various parameters can be automatically calculated to analyze the pulse waveform of MBR averaged in a single heartbeat, 14,[27][28][29][30][31] including the skew, blowout time (BOT), and acceleration time index (ATI), all of which are expressed as absolute values. These new indices have been reported to reflect the augmentation of blood flow resistance basically due to arterial sclerosis as well as aging (i.e., the skew increases and BOT decreases), [27][28][29][30] showing significant correlations with branchial-ankle pulse wave velocity 27 and the stage of glaucoma.…”
mentioning
confidence: 99%
“…10 With recent advances of LSFG, various parameters can be automatically calculated to analyze the pulse waveform of MBR averaged in a single heartbeat, 14,[27][28][29][30][31] including the skew, blowout time (BOT), and acceleration time index (ATI), all of which are expressed as absolute values. These new indices have been reported to reflect the augmentation of blood flow resistance basically due to arterial sclerosis as well as aging (i.e., the skew increases and BOT decreases), [27][28][29][30] showing significant correlations with branchial-ankle pulse wave velocity 27 and the stage of glaucoma. 31 The current study demonstrates functional data to further complement the rationale of circulatory abnormalities as the pathogenesis of CSC, showing sequential changes in these pulse waveform parameters on LSFG.…”
mentioning
confidence: 99%